Pengaruh Pertumbuhan Stek Batang Gempol (Nauclea orientalis L.) dengan Konsentrasi Variasi IBA dan Media Tanaman - Emanuel Maria Yosef Hanoe; Kamaluddin; Yeremias Binsasi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The Gempol plant (Nauclea orientalis L.) is a plant that offers economic benefits, particularly in the wood management industry. Plant stems are one of the primary vegetative growth structures in plants. The growth factor IBA is a growth stimulant in the auxin group. The planting media used include soil, sand, and compost. This study aims to investigate the growth process of Nauclea orientalis L. stems in response to variations in IBA solution concentrations and different plant media. This study uses experimental methods with random group designs. The research activities include preparing plant media, setting up the house, preparing other ingredients, planting, and maintaining the plants. Data is analyzed using variance analysis at a 95% confidence level. Variations in response to gempol growth showed that growth development at 60 days after planting yielded different average results for the number of shoots, root length, number of leaves, leaf length, base weight, and plant dry weight. The highest average number of shoots is achieved with the combination of L3M2 and 5.3 tunas. The highest average yield of tunas was in the L3M4 combination, with 19.3 leaves. The average root length yield with the highest value is achieved with the L2M3 combination, at 20.5 cm. The result of leaf length growth has the highest average in the L0M1 combination, with a value of 21.5 cm.